BFV Homomorphic Encryption Algorithm as a Proposed Encryption Mechanism for the Votenow System of PT XYZ - Muhamad Ikmal Wiawan; Agi Agus Setiawan Sufyan (Knowbase : International Journal of Knowledge in Database, 2025)
Confidentiality and integrity of voting results constitute major challenges in web-based e-voting systems, as vote tallying in conventional approaches still requires data decryption. This condition potentially enables intervention by private key holders and reduces trust in election outcomes. The votenow e-voting platform of PT XYZ does not yet support vote tallying in an encrypted state; therefore, an alternative encryption mechanism is required that does not significantly alter the existing system workflow. This study aims to evaluate the BFV (Brakerski–Fan–Vercauteren) Homomorphic Encryption algorithm as a proposed encryption mechanism for the PT XYZ e-voting system (product name anonymized). A controlled experimental method was applied using a testing prototype with encryption and decryption modules implemented in C++ based on the Microsoft SEAL library, while a PHP-based web interface was employed for data input and visualization. The evaluation assessed the time required to input 50,000 encrypted votes, vote tally accuracy using both decryption-based counting and direct ciphertext computation without decryption, total ciphertext size, verification time for encrypted data validity, ciphertext decryption time, and vote result presentation time. The results indicate that the input of 50,000 votes was completed within 5 minutes, meeting the 10-minute target. Vote tally accuracy reached 100% for both counting methods, and the ciphertext size of 383.4 MB remained below the 512 MB threshold. Furthermore, the encrypted data verification time was recorded at 225.8 seconds, ciphertext decryption time at 5 minutes and 15 seconds, and vote result presentation time via decryption at 13.816 seconds, all of which fall within acceptable operational limits. Based on these findings, the BFV algorithm is considered suitable for adoption as an encryption mechanism in the PT XYZ e-voting system, as it enables vote tallying in the encrypted domain while preserving the confidentiality and integrity of voter data.